Effects of green mussel (Perna viridis) on water quality in shrimp (Penaeus monodon) ponds - Bongo, Nerisa G. (University of the Philippines in the Visayas, 1994)
The present study was conducted to investigate fungi colonizing a woody mangrove species Aegicerascorniculatum and two (2) mangrove associates- Acanhosts thus ilicifolius and Clerodendruminerme. Specifically, this study aims to 1) describe, identify and classify fungi collected on the mentioned hosts and 2) to determine the abundance and frequency of occurrence of fungi collected from these hosts. Results of the study show that Clerodendruminerme had the highest number of species collected (78) ; followed by A. corniculatum (68) ; and A. ilicifolius with only (45) species. This is the first record of fungal mycota reported for C. inerme. There was a relatively high percentage of ascomycetes collected on the three hosts compared with the mitosporic fungi and basidiomycetes. These result imply that the ascomycetes were favored by a relatively more lignocellulosic substrata (A. corniculatum>> C. inerme> A. ilicifolius). The very frequent species (frequency of occurrence > 30%) collected varied on the three hosts : A. ilicifolius- Papulaspora sp.(57%) ; C. inerme- Savoryellalignicola (57%) and Sporidesmium sp. (32%) ; A. corniculatum- Kallichromaglabrum (34%). For the taxonomy of all fungi on three hosts, the ascomycetes are represented by 11 orders, 25 Families, and 43 Genera. Order Dothideales is the most represented Order with 10 families and 13 Genera. For the basidiomycete, it s represented only by 1 Order, 1 Family, and 1 Genus, namely, Melanogastrales, Niaceae, Nia, respectively. For Mitosporic Fungi, they are represented by 29 genera. Primarily the mycota examined are of tropical and marine origin and are associated with woody substrates. The salinity and temperature from August 1997 to July 1998 are at 28-32o/oo and 22-32 C, respectively. The very frequent fungi, namely :Papulaspora sp., Savoryellalignicola, Sporidesmium sp., and Kallchromaglabrum are directly influenced by salinity.